Edukasi pemanfaatan teknologi biogas sebagai sumber energi alternatif di Desa Kuala Terusan Kabupaten Pelalawan, Riau - Muhammad Ariyon; Fitrianti Fitrianti; Idham Khalid; Novia Rita (CANANG: Jurnal Pengabdian Masyarakat, 2022)
Gas is a state asset that can be traded through state-owned or private companies to consumers. The gas produced will be processed in accordance with the regulations and consumer needs. The processing can be channeled directly to consumers or processed in a way that is more consumptive for the community, such as LPG. The use of LPG is now a necessity by the community for kitchen purposes in general. Gas supply is not necessarily evenly distributed, causing people to innovate to find alternatives by utilizing the natural surroundings. One example of nature that can be used as an alternative is to use biogas. This biogas is a solution for people who have not been reached by LPG or have difficulty getting LPG. So that people can create their own alternative energy as a backup without worrying about running out of LPG.